The influence of socioeconomic factors, accessibility and production on the welfare of maize farmers - Sasmita Siregar; Khairunnisa Rangkuti; Rini Sulistiani; Nurhajijah; Syahib Ashiddiq Panggabean (Talenta Publisher, 2026)
Corn (Zea mays L.) is a major food commodity that plays an important role not only as a source of carbohydrates but also as a raw material for various industries. In Indonesia, corn is considered a strategic commodity that can help reduce dependence on rice as a staple food. This study aims to analyze the factors influencing the welfare of maize farmers in Simalungun Regency, North Sumatra, using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The variables examined included socioeconomic factors, accessibility, production, and farmer welfare. Data were collected from 100 maize farmers in Simalungun Regency. The results indicate that socioeconomic conditions, accessibility, and corn production significantly affect farmer welfare. The model produced an R² value of 0.387, suggesting that the independent variables explain 38.7% of the variation in farmer welfare. Measurement model evaluation showed satisfactory validity and reliability, with loading factors above 0.60, Cronbach’s Alpha values above 0.60, Composite Reliability values above 0.70, and Average Variance Extracted values above 0.50, indicating that the model is fit and the latent variables have substantial effects on welfare. The findings imply that improving farmer welfare requires strengthening socioeconomic conditions, enhancing access to production inputs and infrastructure, and increasing farm productivity. Policy support through improved access to capital, agricultural extension services, infrastructure development, and stronger farmer institutions is therefore recommended.